Notebook [35, Spring 1995] - Leier, Mark (James Mark) (Labour/Le Travail, 1995)
The Ontario Ministry of Culture, Tourism, and Recreation has provided funds for research, documentation, and publication of Ontario workplace heritage. In 1994, grants were disbursed for four projects, including a video production on the thirtieth anniversary of the postal workers' strike, a video and booklet focused on preserving workers' heritage in Ottawa, a video tour guide (entitled Mapping the Workers' City) on Hamilton, and a audio documentary on the history of the Northern Ontario labour movement. Takes note of a forthcoming labour conference at the University of Oregon.